BBT307 – Ethnobotany (Etnobotani) July/August 2023 - Pusat Pengajian Sains Kajihayat, PPSK (Universiti Sains Malaysia, 2023)
Second Semester Examination 2022/2023 Academic Session July/August 2023 BBT307 – Ethnobotany (Etnobotani) Duration: 2 hours (Masa : 2 jam)